Effects of biosynthesized zinc oxide nanoparticles as feed additives on growth and hematological parameters of striped dwarf catfish (Mystus vittatus) - Hasan, Md Mahadi; Newaz, Md Shah; Shahariar, Md Arif; Hossain, Md Zunaed; Ahmed, Riad; Alam, Mohammad Shafiqul (Annals of Bangladesh Agriculture, 2025)
Striped dwarf catfish (Mystus vittatus) is a valued freshwater species in South Asia for its taste, nutritional profile, and year-round availability. This study evaluated the effects of biosynthesized zinc oxide nanoparticles (ZnONPs) on the growth performance and hematological parameters of M. vittatus. A total of 960 fish (80/aquarium) were reared in twelve aquariums, and fed diets containing ZnONPs at 0 (T0), 50 (T1), 80 (T2), and 110 (T3) mg/kg for 75 days. Treatment T3 showed the highest weight gain (233.33%), specific growth rate (1.60%/day), and protein efficiency ratio (2.01±0.002), along with the lowest feed conversion ratio (FCR) (p<0.05). Hematological parameters (RBC, Hb, WBC, HCT, etc.) varied numerically, but statistical tests (ANOVA and Kruskal–Wallis) showed no significant differences (p>0.05). Values at 80 mg/kg appeared more stable, though not statistically validated. Effect size analysis indicated large variance explained by treatment for key indices (η² = 0.31–0.39 for RBC, WBC, Hb, HCT). These values suggest biologically meaningful differences that were not statistically confirmed, likely due to small sample size. By contrast, indices with low effect sizes showed minimal treatment influence, indicating real stability across diets. The survival rate (67.50±0.73%) improved with increasing ZnONPs concentrations, reaching the highest in T3 (p < 0.05). Although mortality was a bit higher, likely due to artificial aquarium conditions and early-stage sensitivity, ZnONPs supplementation still showed a positive effect. These findings suggest that dietary ZnONPs at 110 mg/kg improved growth and survivability in M. vittatus without adverse hematological effects. Ann. Bangladesh Agric. 29(1): 89-103